Consumer supply level of red onions in North Sumatra / Dian Habibie … [et al.] - Habibie, Dian; Handayani, Leni; Wahyuni, Sri; Noviani, Nomi (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
Red onion (Allium ascalonicum L) is a vegetable commodity that belongs to the non-substituted spice group, which functions as a cooking spice. Shallots are often a mandatory seasoning in cooking because they are a flavour enhancer for dishes. In addition, shallots are a nutrient-dense food, meaning they are low in calories and high in beneficial nutrients such as vitamins, minerals and antioxidants. The data needed in conducting this research is from 2013-2017, including data on shallot harvest area, shallot productivity, and shallot price in North Sumatra. These data can be obtained from the relevant agencies, namely the North Sumatra Agriculture Office and the Central Bureau of Statistics for North Sumatra Province. Onion harvest area shallot productivity and price have no significant effect on supply. The price elasticity of shallot supply to the cost of shallot itself in North Sumatra is inelastic both in the short and long term.